2021
DOI: 10.3390/v13101966
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Immune Response of T-Cell and B-Cell Subsets in Patients with Moderate and Severe COVID-19

Abstract: Background: The immunological changes associated with COVID-19 are largely unknown. Methods: Patients with COVID-19 showing moderate (n = 18; SpO2 > 93%, respiratory rate > 22 per minute, CRP > 10 mg/L) and severe (n = 23; SpO2 < 93%, respiratory rate >30 per minute, PaO2/FiO2 ≤ 300 mmHg, permanent oxygen therapy, qSOFA > 2) infection, and 37 healthy donors (HD) were enrolled. Circulating T- and B-cell subsets were analyzed by flow cytometry. Results: CD4+Th cells were skewed toward Th2-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2
7

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 69 publications
1
38
2
7
Order By: Relevance
“…2 b and 2c; Supplementary Information Table 1, Online Resource 1). CM Tfh1 reduction has been previously described in the course of the infection or shortly after recovering, but, in opposition to our results, some studies reported and increased percentage of CM Tfh17 in during severe COVID-19, as well as 4–9 weeks after recovering, and no differences 20–26 weeks after recovering [ 13 , 28 , 29 ]. Our data point out important long-term effects of SARS-CoV-2 infection in Tfh cells, translated as a marked decrease in Tfh cell numbers and activation status, as well as an altered polarization pattern, especially affecting Tfh17 cells.…”
Section: Resultscontrasting
confidence: 99%
“…2 b and 2c; Supplementary Information Table 1, Online Resource 1). CM Tfh1 reduction has been previously described in the course of the infection or shortly after recovering, but, in opposition to our results, some studies reported and increased percentage of CM Tfh17 in during severe COVID-19, as well as 4–9 weeks after recovering, and no differences 20–26 weeks after recovering [ 13 , 28 , 29 ]. Our data point out important long-term effects of SARS-CoV-2 infection in Tfh cells, translated as a marked decrease in Tfh cell numbers and activation status, as well as an altered polarization pattern, especially affecting Tfh17 cells.…”
Section: Resultscontrasting
confidence: 99%
“…It is known that the severity of COVID-19 is due to the manifestations of a cytokine storm, which is accompanied by the dysregulation of both innate and adaptive immunity [ 28 , 29 , 30 ]. However, the relationship between vitamin D status and immune markers in patients with COVID-19 is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that, in patients with severe COVID-19, CD4+ Th cells were skewed toward CCR4-expressing Th2-like phenotypes within CD45RA+CD62L− and CD45RA-CD62L− cells, while central memory CCR6+ Th17-like cells were decreased when compared with healthy controls, while patients with moderate COVID-19 had no differences with controls [46]. Furthermore, a Th2 predominance and an increased blood level of Th2 may be closely associated with COVID-19 symptoms, such as intestinal hyperperistalsis, increased acidity of gastric juice and shortness of breath [47]. In addition, an over-reactive CXCR3-CCR6-Th2 cell response was an independent risk factor for death [48].…”
Section: Pathogenesis Of M Tuberculosis (Mtb) and Sars-cov-2 Infectionsmentioning
confidence: 95%